2014
DOI: 10.1063/1.4883186
|View full text |Cite
|
Sign up to set email alerts
|

Radiochemical determination of Inertial Confinement Fusion capsule compression at the National Ignition Facility

Abstract: We describe a radiochemical measurement of the ratio of isotope concentrations produced in a gold hohlraum surrounding an Inertial Confinement Fusion capsule at the National Ignition Facility (NIF). We relate the ratio of the concentrations of (n,γ) and (n,2n) products in the gold hohlraum matrix to the down-scatter of neutrons in the compressed fuel and, consequently, to the fuel's areal density. The observed ratio of the concentrations of (198m+g)Au and (196g)Au is a performance signature of ablator areal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…This scenario portrays the extreme temperature and density conditions of exploding stars. Recent measurements of the neutron activation of gold in the NIF hohlraum suggest that highly excited quasicontinuum states in 196 Au and 198 Au are formed via the 197 Au(n,2n) and the 197 Au(n,γ ) reactions, respectively, in thermal equilibrium with the environment [19,20]. They might interact with the surrounding high energy density plasma before γ decay and, as a consequence, the relative population of the J π = 12 − isomer and the J π = 2 − ground state in gold might be altered.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario portrays the extreme temperature and density conditions of exploding stars. Recent measurements of the neutron activation of gold in the NIF hohlraum suggest that highly excited quasicontinuum states in 196 Au and 198 Au are formed via the 197 Au(n,2n) and the 197 Au(n,γ ) reactions, respectively, in thermal equilibrium with the environment [19,20]. They might interact with the surrounding high energy density plasma before γ decay and, as a consequence, the relative population of the J π = 12 − isomer and the J π = 2 − ground state in gold might be altered.…”
Section: Introductionmentioning
confidence: 99%
“…The sample would then be placed on a high-purity germanium detector for gamma-ray spectroscopic measurements. Based on the initial design of the RACER apparatus, the time between collection and counting is on the order of 1 min [113]. This would allow for measurement of short-lived reaction products that would otherwise not be possible based on current sample retrieval times of >2 h post shot.…”
Section: Magnetic Recoil Spectrometer (Mrs)mentioning
confidence: 99%
“…The larger micrographs were captured with 5× magnification, while the inset micrographs were taken at 40×. [113] and has also been utilized in a fractionation study of NIF target debris [168]. The major advantages of this method are that it allows high-resolution, direct counting of the debris collectors with high-purity germanium detectors after minimal sample preparation time.…”
Section: Grh Diagnostic For Determination Of Ablator Areal Density Inmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is used for the investigation of mass motion in the atmosphere (Nagai et al, 2000), (Yoshimori, 2005) and has been shown to correlate with solar activity (Papastefanou and Ioannidou, 2004). Additionally, experiments at the National Ignition Facility are being planned to study 10 B(p,α) and 3 He(α,γ) reaction cross sections relevant to astrophysics (Rauscher and Raimann, 1996), (Kontos et al, 2013) for which the resulting reaction product, 7 Be, requires collection and quantification with solid radiochemistry collectors (Shaughnessy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%